Influence of Plastic Deformation and Hydroxyapatite Coating on Structure, Mechanical, Corrosion, Antibacterial and Cell Viability Properties of Zinc Based Biodegradable Alloys (MAY, 10.1007/s12540-024-01710-z, 2024) - Aksakal, B.; Isin, Ege; Aslan, N.; Cihangir, S.; Sezek, S.; Yilmazer, Yasemin (Korean Inst Metals Materials, 2024)
[Abstract Not Available]